ผลของเส้นผ่านศูนย์กลางและความยาวของเดือยคอมโพสิตเสริมเส้นใยต่อความต้านทานการล้มเหลวในการบูรณะด้วยเดือยและแกนในฟันที่ได้รับการรักษาคลองรากฟัน - สิริรัตน์ อนันต์วิริยะพร (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The objective of this study was to investigate the failure resistance of root canal treatment (RCT) teeth restored with different diameters and lengths of fiber posts. Forty maxillary central incisors were divided into 4 groups. After root canal treatment, spaces for post were prepared with drill #2. All groups were restored with fiber post (D.T. light-post). The first group used the size that properly fit the canal (post #2). The second and the third group used the post with the same canal length but smaller diameter (post #1) but in third group used resin composite to reinforce the canal. The fourth group used the post that shorter than the canal length but bigger diameter that fit the cervical part of the canal (post #3). After cementing with resin cement (Panavia F 2.0), core build-up with resin composite was performed in each specimen. The teeth were embedded in self cure acrylic resin block. The samples were loaded on a universal testing machine with a crosshead speed of 2 mm/min on the palatal surfaces at 90๐ angle to the long axis of the tooth until failure occurred. Failure resistance of group 1, group 2, group 3, and group 4 were 108.33 ± 11.59 N, 79.08 ± 12.15 N, 119.61 ± 13.03 N, and 94.87 ± 14.48 N, respectively. ANOVA and Bonferroni test revealed that there was no significant difference of the failure resistance between group 1 and group 3 and group 4 (p > 0.05). But group 2 was significantly lower than group 1 and group 3 (p < 0.05). No root fractures occurred in any of the experimental groups. The present study concluded that root canal treatment teeth restored with fiber post that the diameter properly fit the cervical part of canal or used resin composite reinforced the canal space that produced the fiber post fit in the canal were as strong as those restored with the fiber post that the size properly fit in the canal. Restorations with fiber post that smaller diameter than the canal resulted failure resistance significantly decreased.